Sentidos da experiência do trabalho voluntário em uma instituição religiosa - Limberger, Anselmo Matias (2011)
From a phenomenological perspective, the goal in this thesis is to comprehend the meanings of the volunteering experience in a religious institution according to the volunteers. To achieve that goal, the Catholic perspective on volunteerism was outlined, as well as how the volunteering is organized in the Santuário Theotókos. A thorough study over a collaborator who works in the Santuário Theotókos for fourteen years was conducted. The interview was taped, transcribed, synthesized, analyzed and discussed from the phenomenological-psychology approach. The case analysis allowed recognizing the meanings of acceptance experience, belonging, life review, willingness to serve, support, strengthening of identity, among others. The understanding of the case study permitted the creation of growth groups in order to facilitate the volunteering at the Santuário Theotókos and to reflect on the meaning of their own experiences while performing volunteer work focusing on their growth, on the volunteering organization and on its monitoring